EnglishDeveloping A Model with Dematel, Anp, Topsis Approaches for Marketing Strategy Selection in Batik Madura Industry - Indra Cahyadi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2020)
The selection of marketing strategy is very important for the sustainability of small and medium enterprises (SMEs). Choosing the best marketing strategy is a process involving problem of multiple decision-making criteria, which considers many attributes in various phases of a strategy formulation method. This paper proposes a model of selecting marketing strategy for Batik Madura SMEs. The model selected five criteria including customer networking, innovation capabilities, managerial competency, human capital, and company reputation based on literature reviews and focus group decision-making discussion. Analytic network process (ANP), decision-making trial and evaluation laboratory (DEMATEL) and technique for order preference by similarity to an ideal solution (TOPSIS) methods were applied to obtain an impact relation map from each criteria and to determine the priority of marketing strategy. The implementation of the model shows that Batik Madura SMEs should maintain their focus on segmentation marketing as the most appropriate marketing strategy.